DEVELOPMENT OF VOLUNTARY ACTIVITY IN RUSSIA - O. A. Petrina (Вестник университета)
The state of volunteer activity in Russia has been investigated. The implementation of the state policy in relation to volunteerism, the regulatory framework for the development of volunteerism has been analyzed. The stages of formation, institutions of development and support of volunteerism have been considered. The assessment of development of volunteer movement in foreign countries has been given. Barriers, hindering the development of volunteerism have been designated. The algorithm of development of volunteer activity in the regions of the country has been presented. Activation of the volunteer movement and increase of efficiency of activity of the volunteer organizations has been noted.